Effectiveness of removal of hard tissue debris from the mesial root canal system of mandibular molars using different supplementary irrigation protocols: An original study - Neha Sharma; Mohammed A Alobaid; Kamal Nayan; Bharathi Chundi; Piyush Oswal; Hemanth Kumar; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2023)
Introduction: An instrumented and endodontically treated tooth may sometimes impede disinfection by trapping hard tissue as well as the other canal contents at the isthmus level of the canal. Thus, the current in vitro study was piloted to assess the competence of two irrigating systems. Methods: Twenty mandibular with two mesial canals convergent into a single foramen and joined by an isthmus of the human permanent teeth were compared for the two irrigation systems of continuous and intermittent ultrasonic (US) motions of the irrigation. The teeth were prepared by a single rotary system and were imaged using the "Scanning electronic microscopy-SCM". The parameters were compared before and after the irrigation of the canal with the intended US systems for the removal of hard tissue debris. The appropriate statistical tools were used to find the significance, the value of which was kept at P < 0.05. Results: Significant percentage reduction of the hard tissue debris was achieved after the application of the supplemental irrigation protocols (P < 0.05). However between the groups, there was no significant difference. Conclusions: Comparable removal of the hard tissue debris was obtained in both the irrigation systems. Though not significant, the GentleWave performed better than the Irrisafe.